2016
DOI: 10.1016/j.socscimed.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Early life socioeconomic position and immune response to persistent infections among elderly Latinos

Abstract: Persistent infections, such as cytomegalovirus (CMV), herpes simplex virus-1 (HSV-1), Helicobacter pylori (H. pylori), and Toxoplasma gondii (T. gondii), are common in the U.S. but their prevalence varies by socioeconomic status. It is unclear if early or later life socioeconomic position (SEP) is a more salient driver of disparities in immune control of these infections. Using data from the Sacramento Area Latino Study on Aging, we examined whether early or later life SEP was the strongest predictor of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
(76 reference statements)
1
15
0
1
Order By: Relevance
“…However, our study did not find any significant association between the risk of being either anti-CMV IgG or anti-CMV IgM positive with either income or education. Education and income as markers of socioeconomic status have been linked to CMV infection, with lower income and lower level of education being associated with a higher risk of being anti-CMV seropositive (30,32). Zimbabwe has a literacy rate of *87%, ranked position 99 in the world (40), suggesting a fairly uniform and high access of written public health information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study did not find any significant association between the risk of being either anti-CMV IgG or anti-CMV IgM positive with either income or education. Education and income as markers of socioeconomic status have been linked to CMV infection, with lower income and lower level of education being associated with a higher risk of being anti-CMV seropositive (30,32). Zimbabwe has a literacy rate of *87%, ranked position 99 in the world (40), suggesting a fairly uniform and high access of written public health information.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of HIV-infected women was significantly higher ( p < 0.001) (30 years, 25th-75th percentile: 25-34) compared with that of HIV-uninfected women (26 years, 25th-75th percentile: [21][22][23][24][25][26][27][28][29][30][31][32]. The median age of gestation among the pregnant women was 33 weeks (25th-75th percentile: [29][30][31][32][33][34][35][36] and was significantly higher ( p < 0.001) in the HIV-uninfected group (33 weeks, 25th-75th percentile: 30-36) compared with the HIV infected (32 weeks, 25th-75th percentile: [28][29][30][31][32][33][34][35]. The earlier presentation of HIV-infected women to clinic (measured by lower gestation age) could be due to improved healthseeking behavior induced by HIV treatment programs.…”
Section: Demographic Characteristics Of Participantsmentioning
confidence: 99%
“…Since CMV infection is transmitted through contact with infected body fluids, hygiene and hence socioeconomic status are important risk factors for CMV acquisition. The influence of education/literacy on CMV acquisition could be explained by the direct relationship between education and income which determines living conditions [59][60]. A study in Tanzania found urban residence to be a risk factor for CMV seropositivity when compared to rural residence [38].…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…For example, in 2009 Simanek et al showed that educational attainment was significantly associated with seropositivity for CMVand that CMV infection was associated with CVD using data from the NHANES for individuals ages 45 years and older (Simanek et al 2009 reported that CMV seropositivity was higher among adults and children with lower household income and educational levels (using parental data on socioeconomic indicators for the children) (Dowd et al , 2012. More recently, using data from the Sacramento Area Latino study of Aging, Meier et al found that early-life socioeconomic status influences adult probability of CMV infection and that this association was mediated by measures of midlife socioeconomic status (Meier et al 2016). In addition, using data from NHANES, Feinstein et al observed that socioeconomic disparities in all-cause mortality in the US were associated with CMV infection and that this pathway was strongest among older individuals (Feinstein et al 2016).…”
Section: Social and Economic Determinants That Influence CMV Epidemiomentioning
confidence: 99%